Hubungan Kompetensi Sosial dengan Bullying Victimization pada Siswa SMPN X Kabupaten Lima Puluh Kota - Dusatri, Miksa Denola; Yasmin, Maya (YASIN, 2025)
Bullying victimization among adolescents, particularly within school environments, remains a serious issue that negatively affects students. One factor influencing bullying victimization is social competence. This study aims to analyze the relationship between social competence and bullying victimization among students at SMPN X in Lima Puluh Kota Regency. A quantitative correlational approach was employed, with a sample of 194 students selected through proportionate stratified random sampling. Data were collected using instruments developed by the researcher, with the social competence scale based on aspects from Shujja and Malik (2015) and the bullying victimization scale referring to aspects from Smith et al. (1999). Data analysis was conducted using the Pearson Product Moment correlation test. The results showed a significance value of 0.000 (p < 0.05), indicating a significant relationship between social competence and bullying victimization among SMPN X students. Theoretically, this study contributes to psychological research, particularly further studies on the relationship between social competence and bullying victimization at the junior high school level. Practically, the findings underscore the importance of enhancing students’ social competence, especially in the areas of social initiative and leadership. Schools are recommended to implement social competence development programs using empirical methods such as role-playing, digital journalism training, and the provision of safe reporting systems. This research also opens avenues for further studies concerning perpetrator-related factors influencing bullying victimization among students.